A 50nV/√Hz 2‐channel time multiplexed bio‐chopper amplifier with current‐attenuated feedback resistor. Issue 5 (10th December 2021) - Yuk, Beomjin; Kim, Byeongseol; Bae, Joonsung
Abstract: This paper presents 2‐channel time‐multiplexed chopper instrument amplifier for better gain accuracy and mismatch. Mostly, the current‐attenuated feedback resistor with a duty‐cycled resistor is adopted for boosting the RC time constant. It can achieve the high pass corner frequencies between 10 Hz and 320 Hz by a 3‐bit digitally controlled resistor bank of the attenuator. As a result, the instrument amplifier achieves 0.6% gain accuracy between two time‐multiplexed channels, 100 dB CMRR, ‐40 dB crosstalk, and noise densities of 50nV/√Hz. It is implemented in a 180‐nm CMOS technology. It occupies a 0.6 mm*0.6 mm chip area and consumes 1.5μA current consumption from a 1.8 V supply for each channel.